Avaliação do comportamento mecânico através de caracterização experimental e computacional do ácido polilático (pla) em dois diferentes modelos de órteses ortopédicas - Dantas, Victor de Andrade (2019)
The dissemination of the use of 3D printers and the growing concern of the human race with the environment lead to every day projects development which can be obtained through these devices and that are both innovative and sustainable. Thinking about this matter, this work seeks to evaluate the use of polylactic acid (PLA) in temporary orthopedic orthotics for an adult person through experimental tests, with the aid of a correlation analysis of digital images, and finite element computational simulations performed in the program ANSYS®. For this, it was necessary to mechanically characterize the material that the orthoses would be printed. This was done through tensile tests (under ASTM D638 / 14 and D3039 / 14 standards and using the digital image correlation technique) and density evaluation under ASTM D792 / 13 standard. With the results obtained by these analyzes it was possible to create a new material in the library of the ANSYS program with the values of the parameters analyzed. Using this program, we simulated the tensile test that was performed experimentally under the D638 / 14 standard in order to validate the results found with those obtained in the experimental analysis. Then, two different models of orthoses were validated through simulations in their planned and molded geometries. In the latter, the patient's ability to support two different types of effort was verified, one in the planning of the shaped orthosis and the other simulating the movement of the patient's pulse downwards. The results of the parameters obtained in the experimental procedures showed great coherence when compared to other works that use this same material and, mainly, to the product datasheet provided by the manufacturer company. The result of the computational simulation of the tensile test showed a difference of approximately 5% when compared to the same parameter obtained in the experimental test. The analyzes of the two models of orthoses under conditions of similar contours showed a slight difference between the two models, being the model called as model 2 the one which presented smaller values of tensions and total displacements than the first model, in both planned and molded analyzes